Mid-upper arm circumference versus weight for height Z-score for detecting malnutrition in children aged 06-59 months in rural and urban areas of Jabalpur district, Madhya Pradesh, India - Shukla, Nandini; Toppo, Neelam Anupama; Thakur, Aditya; Thakur, Aditya; Kasar, Pradeep Kumar; Sharma, Brajesh (International Journal Of Community Medicine And Public Health, 2020)
Background: WHO and UNICEF propose two independent criteria for diagnosing malnutrition in children aged 6-60 months, viz. mid upper arm circumference and weight-for-height. However, both these criteria do not identify same set of children as having malnutrition, and using only one of the diagnostic criteria proposed by WHO may potentially leave some high-risk children untreated. Therefore, the purpose of this study was to determine the prevalence of malnutrition by using both mid-upper arm circumference (MUAC) and weight for height (W/H) and their differences among children. Methods: Cross sectional study carried out in rural and urban areas of Jabalpur district among 1237 children of age group 06-59 months in randomly selected eight ward and two blocks of Jabalpur district. Where 720 children were from urban wards and 517 from rural villages. Multistage random sampling technique was used for the selection of study subjects. Pre-designed and pretested questionnaire was used for interview, Salter’s Scale for weighing, non-stretchable Measuring Tape for measuring height and Shakir’s tape for mid upper arm circumference. Results: In rural area, prevalence of malnutrition according to MUAC is 74 (14.3%) while according to w/h is 102 (19.7%). While in urban, prevalence according to MUAC is 104 (14.4%) while according to w/h is 136 (18.9%). Conclusions: The findings are clear that, prevalence of wasting by W/H is more than by MUAC. With the use of the currently recommended WHO cut-off for MUAC, a significant number of children would not have been identified. A higher cut off value, therefore recommended for screening.